From Shards to Arts: Regulasi Pengelolaan Serpihan Batu Permata Sebagai Usaha Mencegah Pencemaran Lingkungan di Republik Indonesia dan Thailand - Ronaldo Heinrich Herman (PT. AORSA ADIVISI KAKA, 2026)
This research aims to analyze regulations for gemstone flake management in the Republic of Indonesia and Thailand. Gemstone flakes are waste that has the potential to pollute the environment. Ash from gemstone flakes pollutes rivers and is detrimental to public health. This study argues that gemstone flake waste should be processed into works of art. Mandatory regulations for managing waste into works of art will contribute to preventing environmental pollution in the Republic of Indonesia and Thailand. This research recommends that the Government of the Republic of Indonesia impose sanctions on parties who dispose of gemstone flakes into rivers and do not process them into works of art. Processing gemstone flake waste into works of art will provide legal benefits to the Indonesian people. This doctrinal legal research will use comparative Law approach to analyze laws and previous researchs regarding this legal phenomenon.